2012
DOI: 10.1186/preaccept-3172405466397456
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure changes around satellite repeats on the Schistosoma mansoni female sex chromosome suggest a possible mechanism for sex chromosome emergence

Abstract: Our study provides for the first time evidence for the hypothesis that, at least in organisms with a ZW type of sex chromosomes, repeat-induced chromatin structure changes could indeed be the initial event in sex chromosome emergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, evidence of a functional role of repeats on vertebrate sex chromosomes is limited at this stage, largely due to the difficulty in obtaining Y Advances in Evolutionary Biology 5 or W chromosome sequences. Nonetheless, methods have been developed to achieve this challenging task [88,89] and will undoubtedly lead to more studies in this area. Again, we are able to gain important insight into the function of sex chromosome repeats from species outside the vertebrate lineage.…”
Section: Do Sex Chromosome Repeats Have a Function?mentioning
confidence: 99%
See 3 more Smart Citations
“…However, evidence of a functional role of repeats on vertebrate sex chromosomes is limited at this stage, largely due to the difficulty in obtaining Y Advances in Evolutionary Biology 5 or W chromosome sequences. Nonetheless, methods have been developed to achieve this challenging task [88,89] and will undoubtedly lead to more studies in this area. Again, we are able to gain important insight into the function of sex chromosome repeats from species outside the vertebrate lineage.…”
Section: Do Sex Chromosome Repeats Have a Function?mentioning
confidence: 99%
“…The Z and W chromosomes can be cytogenetically distinguished by their chromatin structure rather than by their size. Sequencing of male and female genomes led to the identification of W-specific sequences, which consisted of 36 W-specific repeats, including an SMalpha retroposon, LTRs, LINE2, and DNA transposons [89]. Of these repeats, transcription was detected for eight, and three of these were transcribed in the larval stages but not in immature or adult females.…”
Section: Do Sex Chromosome Repeats Have a Function?mentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, genetic linkage map analysis by crossing a female of one S. mansoni strain to a male of another strain coupled with chromosome mapping with BAC (bacteria artificial chromosome) clones identified a non-recombination site between the Z-and W-specific genes (Criscione et al 2009). Lepesant et al (2012) gave suggested chromatin structural changes around the W-specific repeats are responsible for the initial event (non-recombination) in sex chromosome development. However, whether structural changes caused by inversions are part of the mechanism that resulted in the differentiation of the ZW remains to be determined and is the main subject of the present study.…”
Section: Schistosomiasis a Human Infection By Blood Flukes In The Genusmentioning
confidence: 99%